Awas pada Badan untuk Menurunkan Gejala Somatis di Tengah Pandemi COVID-19 - Rahmandani, Amalia; La Kahija, Yohanis Franz (Jurnal Psikologi Teori dan Terapan, 2021)
The World Health Organization declared Corona Virus Disease 2019 (COVID-19) as a pandemic disease. The psychological impacts of the pandemic can increase the risk of somatic symptoms among individuals. As a signal of alertness and adaptive action, prolonged somatic symptoms can affect overall psycho-physiological functions. When the symptoms continue with a decrease in individual immunity, COVID-19 infection can become riskier. This study aims to examine the effect of using body awareness to reduce somatic symptoms through a short intervention in people in the middle of COVID-19 pandemic. Intervention was conducted online in accordance with the directives of the Indonesian government concerning social restrictions. This study used one group pretest-posttest design. Data were collected using Somatic Symptom Scale (SSS-8) which was adapted into Indonesian. There were 34 subjects fully participated in this intervention based on convenience sampling through online publication (voluntary participation). Using the paired sample t-test, the results show that body awareness provides significant benefits in decreasing somatic symptoms.Keywords: Body awareness, COVID-19 pandemic, somatic symptomsÂ Abstrak: World Health Organization menyatakan Corona Virus Disease 2019 (COVID-19) sebagai penyakit pandemik. Dampak psikologis dari pandemi dapat meningkatkan risiko munculnya gejala somatis yang dirasakan oleh individu. Gejala somatis sebagai sinyal untuk waspada dan adaptif dapat berkepanjangan dan memengaruhi fungsi psikofisiologis secara menyeluruh. Gejala somatis yang berkepanjangan dan disertai penurunan imunitas individu dapat meningkatkan risiko terinfeksi COVID-19. Penelitian ini bertujuan menguji pengaruh intervensi singkat â€œawas pada badanâ€ terhadap penurunan gejala somatis pada masyarakat di tengah pandemi COVID-19. Intervensi dilakukan secara daring sesuai arahan pemerintah terkait pembatasan sosial. Penelitian menggunakan one group pretest-posttest design dengan menggunakan Somatic Symptom Scale (SSS-8) yang telah diadaptasi ke dalam Bahasa Indonesia sebagai instrument pengumpul data. Terdapat 34 partisipan yang direkrut berdasarkan convenience sampling melalui publikasi online dan mengikuti intervensi secara penuh (partisipasi sukarela). Hasil analisis menggunakan paired sample t-test menunjukkan bahwa latihan â€œawas pada badanâ€ memberikan manfaat signifikan bagi penurunan gejala somatik.